Food neophobia: explored and unexplored terrains - Subramaniam, Anusuiya; Muthusamy, Geetha (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2024)
Food neophobia is beingregarded as an individuals’ reluctance to tryunfamiliar or novel food and consequently the inclination to stayaway from it. In addition, unfavorable taste, odorand appearance of novel foods signifies the definition of neophobia. Since research pertaining to food neophobia is limited,reviewis aimed at exposing the disparity in research on past, current and future trends pertaining to research on food neophobia. Studies on food neophobia are essential as food neophobia has impact on food preferences. Understanding the factors influencing foodpreferences is vital for implementing and promoting positive changes inthe food habits of any society. The identification and compilation of all food neophobia-related publications covered publications produced between 2010 and 2020. Articles wereselected from the three most prominent and popular online databases/search engines, namely 1) EBSCOHost (http://search.ebscohost.com), 2) Science Direct (http://www.sciencedirect.com), and 3) Google Scholar (http://scholar.google.com). Based on the results, a thorough analysis was achieved concerning the following: (1) theory pertaining to food neophobia, (2) measures of food neophobia, (3) importance of research pertaining to food neophobia, (4) researches on food neophobia, and (5) directions for future research on food neophobia. The study concerning food neophobia is essential as food neophobia influences food preferences. Understanding the factors prompting food preferences is crucial towards the implementation and promotion of positive changes in the food habits of any society. This study adds to the academia and industry by discovering several inadequacies in the existing studies and bestowing an outline for future research. Further studies are certainly imperative to empirically authenticate the concept of food neophobia through systematic investigations and devise a means to quantify it.